Indigenous peoples' participation in the management of Balinese cultural tourism - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini; Ni Ketut Sari Adnyani (Legality : Jurnal Ilmiah Hukum, 2021)
The purpose of this research is to examine the participation of indigenous peoples in the management of Balinese cultural tourism and the supporting elements of indigenous people's participation. The type of research used is normative legal research with a statutory approach. The population of this research is 1,495 traditional villages in Bali Province using samples in South Bali and North Bali. The results showed that Ayung Traditional Village as part of the South Bali Region initially did not heed the Tri Hita Karana concept which was in accordance with the provisions of the implementation of Balinese cultural tourism. A comparative study with the Penglipuran traditional village provides input on the participation of the Ayung traditional village in the management of cultural tourism. The supporting elements of cultural tourism management in Bali require approval, readiness, and availability of the space carrying capacity of the Ayung traditional village in relation to the environment. It is important for the local government of Bali Province to coordinate spatial planning with traditional villages in tourism areas because the involvement of traditional villages greatly determines the existence of Balinese cultural tourism by compiling customary village-based spatial planning regulations.